Developing a Framework for Implementing Public Private Partnerships in a Research Reactor Project in the United Arab Emirates - Almarri, Khalid (2015)
Public private partnerships (PPP) procurement instruments have been very popular tools for developing projects around the world. This is largely due to their success in bringing quality, efficiency, innovation, funds, experience, and most importantly risk sharing to the projects they are involved in. The UAE is currently developing a peaceful nuclear energy program in response to the future demands. Research is required to support nuclear energy generation projects in order to maximize their performance. Research of this type will require a research reactor to be developed, which will also benefit other industries such as transportation, health services, construction, petro chemicals, in addition to technical colleges and R&D facilities. Collaborations between government and private parties through public private partnerships (PPP) can maximize the benefits expected from the adoption of a research reactor project. The aim of this research is to develop a framework for establishing a research reactor (RR) project in the UAE through the utilisation of public private partnerships (PPP). The aim of this study was arrived at in three steps. The first step was thorough literature research of detailed investigative works to identify the best practices in PPP implementation globally and customizing it for the establishment of a generic PPP framework for the UAE. Through the qualitative content analysis approach, assisted by Nvivo software, a five-stage generic framework was produced. Second, a questionnaire was used to draw data for the establishment of the PPP critical success factors for the UAE, in which data was collected from 30 participants from the UAE and 62 participants from the UK. The participants were PPP practitioners or researchers. This enabled the comparative analysis process to add a local dimension to the generic framework. Finally, semi-structured interviews conducted with 10 experts in the field of research reactors, using grounded theory method, established the success factors for research reactors. These factors would be unique in the sense that they complement the implementation of the PPP framework in the research reactor project while staying within the UAE context. The findings of the comparative analysis of the two samples between the UAE and the UK showed a significant similarity in PPP practice trends between the two in the three areas analysed; attractive factors, value for money factors, and the critical success factors. The core phenomenon that impairs the success of research reactors was identified to be underutilization. Causal conditions that stemmed from project initiation work were found to be the main sources of said underutilization. This included the reduction of government intervention to help mitigate the risk of underutilization. The contextual conditions responsible for creating these circumstances were of both local and regional contexts and viability. The practical implications of this research are mainly related to the development of the first PPP framework for the UAE, and more specifically for a research reactor project. The contributions of this research to the body of knowledge are related to the highlighted similarities and differences in the practice between the UAE and the UK, which opened areas for future consideration. In the research reactor field, the identified causal, intervening, and contextual conditions opened new areas for future research.